Kepatuhan Syariah Pada Fintech Lending Syariah: Analisis Akad dan Implementasinya - Ahmad Fathorrozi; Moh. Hamzah (Qawanin: Jurnal of Economic Syaria Law, 2024)
Islamic fintech lending has emerged in response to the need for financial products that comply with Islamic law. In the context of Muslim communities, fintech lending is assessed not only in terms of efficiency and convenience but also for its adherence to Sharia principles. This research is of a normative-empirical type with a content analysis approach. The results of this study indicate that Islamic fintech is a financial innovation that combines technology with Islamic Sharia principles. Parties involved need to understand the contracts used according to their needs, such as sales (al-al-bayʿ), muḍārabah, mushārakah, wakālah bil ujrah, and qardh, the permissibility of which is explained in the Qur'an and rational evidence. In Indonesia, Islamic fintech activities refer to DSN-MUI Fatwa Number 117/DSN-MUI/II/2018. With Islamic values and strict government regulations, economic operations can be conducted in a beneficial, just manner, avoiding riba (usury), maysir (gambling), and gharar (uncertainty).